Effect of high temperature on physical and mechanical properties of Jalore granite - Gautam, P.K.; Verma, A.K.; Jha, M.K.; Sharma, Pushpendra; Singh, T.N. (Journal of applied geophysics, 2018)
Underground nuclear waste disposal is an important area of research which requires concepts related to thermal cracking in brittle rock. The disposed canister produces residual heat that results from the decay of radionuclide's; increase the heat in the surrounding rock.The changes of mineral composition and pore water content of the rock after heating lead to the variation of the physical and mechanical properties of the host rock. In this study, an experiment was carried out to study the thermal effect (from 25 °C to 600 °C) on stress-strain behavior, elastic modulus, peak stress, thermal damage, and tensile strength of Jalore granite, India and compared with similar properties of granite from other countries. Scanning electron microscope (SEM) analyses have been done to determine the changes in growth of thermal cracks due to heating of Jalore granite at different elevated temperature. Based on the temperature interval (between 25 °C and 600 °C) can be divided into two zones from 25 °C–300 °C to 300 °C–600 °C. It was observed that the compressive strength and tensile strength of rock increased as the temperature was gradually increased up to 300 °C, but decreased sharply above this temperature. In the temperature range of 300 °C–600 °C, stress-strain curves showed plasticity behavior in which brittle-ductile transition was observed. It was observed that thermally-inducedmicro-cracks because of its complexity in thermal expansivity, the densification stage is longer which increases the crack density rapidly, at the same time, the elastic modulus, compressive strength, and thermal damage are higher. Heating at high temperature will make the tensile strength of granite change due to the loss of water and minerals and the effect of thermal stress that the most conspicuous effect is the expansion of quartz.It is found that 300 °C is the critical temperature for Jalore granite above which the physicomechanical behavior reduces sharply. A very strong correlation was found between the compressive strength and tensile strength of Jalore granite rock with very high coefficients of determination. •The thermal effect (25–600 °C) on both physical and mechanical parameters of granite was studied.•A threshold temperature range of rock was found and heating rate was recognized by multiple tests.•Experiments demonstrate crack propagation stress threshold ratios of granite after high thermal treatment.•A comparative study has been carried out against similar work with other granites around the world.